The Role of E-Education Marketing Strategy in the Development of Educational Institution Customers at Bank Sumatra Syariah - Apriyanti, Vivi; Setiadi, Iwan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study aims to analyze the role of e-education marketing strategies in developing educational institution customers at Bank Sumatra Utara Syariah. With a qualitative approach, data was obtained through in-depth interviews, participatory observations, and documentation studies from several educational institutions that are bank customers. The results of the study show that the e-education marketing strategy, which includes the provision of digital payment platforms, financing of educational technology infrastructure, and Sharia-based scholarship programs, significantly improves the efficiency of financial management and supports the digital transformation of educational institutions. This strategy has also succeeded in increasing the number and loyalty of customers from the education sector, especially Islamic-based educational institutions that respect Sharia principles in banking services. However, challenges such as limited technological infrastructure in rural areas and lack of service socialization still need to be overcome. This study concludes that the right e-education marketing strategy can play an important role in customer development and support the digitalization of education in Indonesia. The recommendations include increasing socialization and service innovation that is more in line with the needs of educational institutions.